The Influence of the Technology Acceptance Model on Personal Branding Through Self-Efficacy on LinkedIn Among Generation Z - Saragih, Fry Melda; Cristian, Nico (Universitas Ibn Khladun Bogor, 2025)
This research investigates how perceived usefulness and perceived ease of use influence personal branding, with self-efficacy acting as a mediator, among Generation Z LinkedIn users in Indonesia. As digital natives, Gen Z increasingly leverages social media for career development, with LinkedIn being a key platform for personal branding. Grounded in the Technology Acceptance Model (TAM), this quantitative study collected data from 150 participants and applied Partial Least Squares Structural Equation Modeling (PLS-SEM) for analysis. Findings reveal that perceived usefulness and ease of use do not directly impact personal branding; rather, they significantly boost self-efficacy, which in turn strongly affects personal branding. Mediation analysis shows that self-efficacy fully mediates the relationship between technology acceptance factors and personal branding. These results highlight the importance of psychological readiness, beyond functional perceptions, in successful personal branding. Limitations include the study’s cross-sectional design and reliance on self-reported data. Future studies might explore other moderating or mediating variables such as digital literacy, intrinsic motivation, or peer influence, as well as the longitudinal development of self-efficacy in forming digital professional identities.